2016
DOI: 10.4038/sljid.v6i2.8119
|View full text |Cite
|
Sign up to set email alerts
|

Combating Antimicrobial Resistance

Abstract: Antimicrobial Resistance (AMR) is a key global health challenge. While numerous strategies have been put forward by different organizations to combat this problem, identification of locally relevant issues that drive resistance and addressing them would be the key to success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The misuse of common antibiotics is very high. An increase in antibiotic resistance development and the occurrence of multiple drug resistance have been observed in hospital settings (Liyanapathirana and Thevanesam 2016). This is an area that needs due attention since almost all municipalities producing compost using solid waste in Sri Lanka are not segregating materials based on their biological safety.…”
Section: Human Faeces As a Source Of Raw Materials In Compostingmentioning
confidence: 99%
See 1 more Smart Citation
“…The misuse of common antibiotics is very high. An increase in antibiotic resistance development and the occurrence of multiple drug resistance have been observed in hospital settings (Liyanapathirana and Thevanesam 2016). This is an area that needs due attention since almost all municipalities producing compost using solid waste in Sri Lanka are not segregating materials based on their biological safety.…”
Section: Human Faeces As a Source Of Raw Materials In Compostingmentioning
confidence: 99%
“…Antibiotics are the most successful and sometimes the only treatment against infectious diseases caused by bacteria and fungi. However, the spread of antibiotic resistance traits among pathogenic groups of microorganisms is challenging the healthcare systems worldwide including Sri Lanka (Martinez 2009;Pruden et al 2013;Liyanapathirana and Thevanesam 2016). Antibiotic residues, antibioticresistant bacteria, and genetic information containing antibiotic resistance genes (free DNA) are considered as antibiotic resistance determinants (Martinez 2009).…”
Section: Antibiotic Resistance Determinantsmentioning
confidence: 99%
“…(10) Another study done in a State tertiary care hospital in 2009 showed that Acenetobacter spp responsible for Ventilator Associated Pneumonia (VAP) were multidrug resistant with resistance rates of 90% to cefotaxime, 73.3% to ceftazidime, 70% to imipenem, and 53% to cefoperazonesulbactam. (11) Concerns with AMR are further exacerbated in Sri Lanka as there is no functioning of an official surveillance system although the strategic plan to curb AMR was officially launched with celebrations in 2017. Thailand developed its national strategic plan on AMR around the same time as Sri Lanka but unlike us, has gone further to set targets one of which is for a reduction in AMC in humans by 20% in 2021.…”
Section: Disscussionmentioning
confidence: 99%
“…HAIs are believed to be an indicator of how well and how safely patients are being cared for [1]. Humans are affected by the global problem of antimicrobial resistance (AMR), which has grown to be a major obstacle to contemporary medicine [2]. Methicillin was formerly recognized as an antibacterial that was used to treat a variety of illnesses caused by S. aureus, but it quickly gained acceptance in medicine and eventually encouraged the development of bacteria strains that were resistant to it [3].…”
Section: Introductionmentioning
confidence: 99%